Strategy and Role of Health Promotion in Stunting Prevention: Literature Review - Katmini, Katmini; Yunita, Astri (Poltekkes Kemenkes Surakarta, 2025)
Background: Currently, Indonesia is facing health problems suffered by children under five due to malnutrition or malnutrition which causes stunting. Based on data from the Indonesian Nutrition Status Survey (SSGI), it shows that the prevalence of stunting in Indonesia in 2023 will reach 21.5%. Health Promotion is considered a collaboration of educational and environmental support to create healthy living behavior for the entire community. The purpose of this literature review is to determine the Strategy and Role of Health Promotion in Stunting Prevention. Methods: In writing this literature review article, literature searches were conducted systematically using various scientific databases such as PubMed, ScienceDirect, and Google Scholar. The keywords used were adjusted to the research topic, including stunting, health promotion, and prevention. Inclusion criteria included articles published within the last five years (2019-2024), written in English or Indonesian, and directly addressing the topic under review. At the beginning of the article search, the authors found 65 articles, then selected according to the criteria to 24 articles, then narrowed down to 5 articles. Results: Based on the results of several articles analyzed, show that preventive and promotive efforts are the right efforts to prevent stunting from 1000 HPK (First Day of Life). The health promotion strategy itself is divided into 3 aspects, including advocacy, social support, and community empowerment. Conclusion: Thus, it is hoped that preventive and promotive efforts will be intensified to reduce the prevalence of stunting in Indonesia. The government supports this by launching the Healthy Indonesia Program which consists of 3 pillars, the healthy paradigm, strengthening health services, and National Health Insurance (JKN).